Effect of Presenilin Mutations on APP Cleavage; Insights into the Pathogenesis of FAD - Li, Nuomin; Liu, Kefu; Qiu, Yunjie; Ren, Zehui; Dai, Rongji; Deng, Yulin; Qing, Hong (Frontiers in Aging Neuroscience, 2016)
Alzheimer disease (AD) is characterized by progressive memory loss, reduction in cognitive functions, and damage to the brain. The β-amyloid precursor protein can be sequentially cleaved by β- secretase and γ-secretase. Mutations in the presenilin1（PS1） are the most common cause of Familial Alzheimer’s disease ( FAD). PS1 mutations can alter the activity of γ-secretase on the cleavage of the β-amyloid precursor protein, causing increased Aβ production. Previous studies show that the βAPP-C-terminal fragment is first cleaved by β-scretase, primarily generating long fragments of Aβ48 and Aβ49, followed by the stepwise cleavage of every three amino acid residues at the C terminus, resulting in Aβ48-, 45-, 42 line and Aβ49-, 46-, 43-, 40 line. Here, we used LC-MS/MS to analyze unique peptides IAT, VVIA, ITL，TVI，IVI through sequential cleavage, combined with ELISA to test the level of Aβ42 and Aβ40 for validation. The results show that most FAD mutant PS1 can alter the level of Aβ42 and Aβ40 monitored by the Aβ42/Aβ40 ratio. Among them, 6 mutants (I143T, H163P, S170F, Q223R, M233V and G384A) affect the Aβ42/40 ratio through both Aβ49-40 and Aβ48-38 lines; L166P through decreasing the Aβ49-40 line, 6 mutants (I143V, M146V, G217A, E280A, L381V and L392V) through increasing the Aβ48-42 line. More importantly, we found some mutations can affect the γ-secretase cleavage preference of α-CTF and β-CTF. In conclusion, we found that the FAD PS1 mutations mainly increase the generation of Aβ42 by decreasing the cleavage of Aβ42-Aβ38 and Aβ43-Aβ40.